Perceived Social Support as a Mediator of Cognitive Functioning in Older Adults: A Cross-Sectional Study in Rural Communities - Željko Mudri (22681679) (2025)
The sample included 265 older adults aged 65 years and above, recruited using snowball sampling between March and July 2025 in rural communities. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA), and perceived social support was measured with the Multidimensional Scale of Perceived Social Support (MSPSS). Data were analyzed using descriptive and inferential statistics in JASP, with a significance level set at p < 0.05.